Non-Fermi liquid behavior in the layered NaxCoO2 - Zorkovská, A.; Šebek, J.; Šantavá, E.; Bradaric, I.; Feher, A. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2007)
The specific heat in the temperature region of 100 mK–360 K and in magnetic fields of 0 and 9 T, as well as the susceptibility from 2 to 360 K and in a magnetic field of 1 T have been measured in the layered NaxCoO2 (x = 0.65, 0.70, and 0.75) oxides. Analysis of the data revealed non-Fermi liquid behavior. The character of the observed anomalies seems to be connected to the mesoscopic phase separation, underlining the impact of disorder on the low-lying excitations in cobaltates.